Three-dimensional 1T-SnS2 wrapped with graphene for sodium-ion battery anodes with highly reversible sodiation/desodiation. (1st April 2022) - Li, Zhao; Zheng, Jialu; Xiao, Meixia; Jiang, Hao; Wang, Lei; Song, Haiyang; Gao, Huan-Huan
Abstract: Sodium-ion batteries have attracted tremendously significant attention as an alternative to Li-ion batteries due to the similar electrochemical properties. However, owing to the larger atomic radius of sodium, the sodium-ion batteries have been inevitably suffered from the inferior electrochemical reaction kinetics and descending cyclic stability, limiting its practical applications. Here, sodium-ion batteries based on 3D 1T-SnS2 /RGO composite electrode with highly reversible sodiation/desodiation process are realized through a facile CVD process and spray coating. It displays excellent initial specific charge and discharge capacities (766.7 mAh g −1 and 768.8 mAh g −1 ), after 100th cycle, the charge and discharge capacities are 648.1 mAh g −1 and 650.8 mAh g −1, respectively, with 84.6% capacities retention ratio, indicating the excellent reversibility and high electrochemical reaction kinetics. The composite sodium-ion battery anode still delivers high specific capacities of 865.6 mAh g −1, 758.2 mAh g −1, 678.5 mAh g −1, 581.2 mAh g −1 and 503.8 mAh g −1 at the current density of 0.1 C, 0.5 C, 1 C, 2 C and 5 C, respectively, indicating its excellent reversible sodiation/desodiation reaction and rate capability. This work confirms the high potential of the SnS2 -based anode for SIBs from its highly reversible capacity and excellent rate capability and points out the significance of the rational design of three-dimensional composite anode with high reversibility and electrochemical reaction kinetics. Graphical abstract: Sodium-ion batteries based on 3D binder-free 1T-SnS2 /RGO composite electrode with highly reversible sodiation/desodiation process are realized through a facile ion milling evaporation, CVD process and spray coating. It displays excellent initial specific charge and discharge capacities (766.7 mAh g −1 and 768.8 mAh g −1 ), after 100th cycle, the charge and discharge capacities are 648.1 mAh g −1 and 650.8 mAh g −1, respectively, with 84.6% capacities retention ratio, indicating the excellent reversibility and high electrochemical reaction kinetics. The composite sodium-ion battery anode still delivers high specific capacities of 865.6 mAh g −1, 758.2 mAh g −1, 678.5 mAh g −1, 581.2 mAh g −1 and 503.8 mAh g −1 at the current density of 0.1 C, 0.5 C, 1 C, 2 C and 5 C, respectively, indicating its excellent reversible sodiation/desodiation reaction and rate capability. Image, graphical abstract